Is thrombolysis beneficial in elderly patients with minor ischemic stroke? - Naess, Halvor (Frontiers in Stroke, 2024)
A pooled analysis of data from randomized controlled trials showed that thrombolysis is an effective treatment in patients over 80 years of age with acute ischemic stroke. However, the outcome in daily clinical practice may differ from those observed in randomized controlled trials. Thus, the aim of the present study was to compare short-term outcome as to thrombolysis or not in patients >80 years of age with ischemic stroke or TIA admitted to Haukeland University Hospital in Norway.All patients with acute ischemic stroke or TIA >80 years of age admitted to Haukeland University Hospital within the 4.5 hours time window after stroke onset between 2006 and 2020 were prospectively included in this observational study. Patients who received thrombolysis were compared to patients not receiving thrombolysis. The endpoint was modified Rankin Scale (mRS) score day 7 or on discharge if earlier. National Institute of Health Stroke Scale (NIHSS) scores were recorded repeatedly during the hospital stay.In total 808 patients were included. Thrombolysis was given to 393 (49%) patients. In patients with NIHSS score <3 (minor ischemic stroke) at admission thrombolysis was associated with worse shortterm outcome (beta=.13, P=.03) whereas thrombolysis was associated with better short-term outcome in patients with NIHSS score ≥3 (major ischemic stroke) at admission (beta=-.12, P=.003).Thrombolysis appeared to be associated with neurological worsening in patients with NIHSS score<3 at admission. Excluding patients who underwent thrombectomy, did not change the results.In elderly patients with major ischemic stroke, thrombolysis was associated with better short-term outcome. However, in patients with minor ischemic stroke, thrombolysis was associated with worse short-term outcome. Several reasons for this discrepancy are discussed.